Define Intervention (The Biblical archaeology review, 2025)
What is a "pesher"? 1. A type of grinding tool 2. A biblical song or hymn 3. A type of biblical commentary 4. Part of a camel’s harness 5. An ancient list of tribes or cities Answer: (3) A type of biblical commentary A pesher (plural: pesharim) is a distinctive style of biblical commentary known most famously from the Dead Sea […]